The Proliferation of Anomalous Digital Fatwas: A CriticalExamination of Jurisprudential Challenges and Societal Impactsin the Digital Age - Ali, Abdelhalim Mohamed Mansour; Aljahsh, Muhammad Ahmad Ibrahim (Universitas Islam Negeri Jakarta, 2025)
This paper investigates the emergence and proliferation of anomalous digital fatwas—online religious decrees that deviate from established Islamic legal principles, and their impacts on Islamicjurisprudence and social cohesion. It adopts a qualitative exploratory approach. It uses a systematicliterature review and case study analysis to examine the factors contributing to the rise of these fatwas and their implications for the Muslim community. Key findings reveal that digital platforms have transformed traditional religious authority structures, enabling the rapid and unvetted dissemination of religious verdicts. The analysis further highlights the role of external pressures, ideological biases, and limited jurisprudential oversight in exacerbating this problem. The paper proposes practical solutions, including enhanced digital literacy training for muftis, the establishment of formal regulatory frameworks for fatwa verification, and the promotion of collaborative scholarly deliberation. The implications of this research extend beyond academia to offer actionable strategies for religious institutions, policymakers, and community leaders seeking to foster social harmony in an increasingly interconnected digital landscape. Abstrak Artikel ini mengkaji kemunculan dan proliferasi fatwa digital yang menyimpang—keputusankeagamaan online yang menyimpang dari prinsip-prinsip hukum Islam yang mapan—dan dampaknya terhadap yurisprudensi Islam dan kohesi sosial. Studi ini mengadopsi pendekatan eksplorasi kualitatif, memanfaatkan tinjauan literatur yang sistematis dan analisis studi kasus untuk menguji faktor-faktor yang berkontribusi terhadap maraknya fatwa-fatwa ini dan implikasinya bagi komunitas Muslim. Temuan-temuan utama mengungkapkan bahwa platform digital telah mengubah struktur otoritas keagamaan tradisional, memungkinkan penyebaran fatwa agama yang cepat dan tidak disaring. Analisis ini lebih lanjut menyoroti peran tekanan eksternal, bias ideologis, dan pengawasan yurisprudensi yang terbatas dalam memperburuk masalah. Untuk mengatasi tantangan-tantangan ini, artikel ini mengusulkan solusi-solusi praktis, termasuk peningkatan pelatihan literasi digital bagi para mufti, pembentukan kerangka peraturan formal untuk verifikasi fatwa, dan promosi musyawarah ilmiah kolaboratif. Implikasi dari penelitian ini melampaui akademisi, menawarkan strategi yang dapat ditindaklanjuti bagi lembaga-lembaga keagamaan, pembuat kebijakan, dan pemimpin masyarakat yang berupaya untuk menumbuhkan harmonisasi sosial dalam lanskap digital yang semakin saling berhubungan.